THE INTERNALIZATION OF ISLAMIC MORAL VALUES IN COUNTERING THE DIGITAL GENERATION'S ETHICAL CRISIS: An Integrative Study of Al-Ghazali and Franz Rosenthal's Thought - Ahmad Fauzi Rahmatullah; Siti Nurhalimah (Karimiyah: Journal of Islamic Literature and Muslim Society, 2025)
This study investigates strategies for internalizing Islamic moral values as a systematic response to the ethical crisis confronting the digital generation. The proliferation of digital technology has engendered dual consequences: the democratization of knowledge access and the concurrent erosion of moral foundations rooted in Islamic tradition. Employing a qualitative-descriptive approach grounded in critical library research (library research), the study analyzes the ethical thought of Franz Rosenthal as articulated in The Muslim Concept of Freedom (1960) and al-Ghazali's Bidayatul Hidayah (eleventh century, Indonesian edition 2019) as primary theoretical frameworks, triangulated with peer-reviewed empirical literature published between 2018 and 2023. Forty-seven articles meeting rigorous inclusion criteria were subjected to systematic content analysis. Findings reveal that the digital ethics crisis manifests across four interconnected dimensions: moral identity disorientation, online disinhibition, moral consumerism, and attention fragmentation. In response, the study identifies three evidence-based internalization strategies: (1) ta'wid digital systematic ethical habituation aligned with al-Ghazali's methodology of repetitive virtuous practice; (2) uswah hasanah reconstructed role-modeling adapted to the influencer-driven digital ecosystem; and (3) tarbiyah ruhiyah integration of spiritual formation into digital educational curricula. These strategies are synthesized into the Integrative Islamic Moral Internalization Model (MIINMI), a three-layered framework encompassing cognitive-theological, affective-spiritual, and behavioral-habitual dimensions. The study concludes that universal Islamic values amanah, 'adl, ihsan, and tawadu' constitute contextually relevant and empirically supported antidotes to moral degradation in the digital era, offering a transcendent normative grounding that secular character education models lack.